Nutritional traditional and complementary medicine strategies in pediatric cancer: A narrative review. (2nd July 2020) - Diorio, Caroline; Kelly, Kara M.; Afungchwi, Glenn M.; Ladas, Elena J.; Marjerrison, Stacey
Abstract: Traditional and complementary medicine (T&CM) strategies are commonly used by pediatric cancer patients. Nutritional approaches to T&CM include bioactive compounds, supplements, and herbs as well as dietary approaches. Pediatric cancer patients and their families commonly request and use nutritional T&CM strategies. We review the potential risks and benefits of nutritional T&CM use in pediatric cancer care and provide an overview of some commonly used and requested supplements, including probiotics, antioxidants, cannabinoids, vitamins, turmeric, mistletoe, Carica papaya, and others. We also discuss the role of specific diets such as the ketogenic diet, caloric restriction diets, whole‐food diets, and immune modulating diets. There is a growing body of evidence to support the use of some T&CM agents for the supportive care of children with cancer. However, further study is needed into these agents and approaches. Open communication with families about T&CM use is critical.